Beberapa Bahan Obat dan Ritus dalam Pengobatan Tradisional di Tonsea-Minahasa - B.H. Moningka (Antropologi Indonesia, 1995)
This paper a preliminary observation of drug materials, treatments, rites, and traditional concepts on diseases which are usually used at Tonsea-Minahasa...[...] According to the traditional concept given by traditional healer, all diseases can be classified in four groups related to the cause and the origin of diseases, as follow: (i) diseases due to bad vapor or bad wind of the earth, (ii) diseases due to improper care, (iii) diseases due to black magic, (iv) diseases due to the practice of "Opo-opo". Some traditional materials presented in this paper have not been well identified taxonomically. Further pharmacological investigations of these traditional drug materials are expected in the near future.